Quality control and purification of ready-to-use conjugated gold nanoparticles to ensure effectiveness in biosensing - Wang, Junjie; Giordani, Stefano; Marassi, Valentina; Roda, Barbara; Reschiglian, Pierluigi; Zattoni, Andrea (Frontiers in Sensors, 2022)
Introduction: Gold nanoparticles (AuNPs) and their conjugates are used for many applications in the field of sensors. Literature lacks procedures able to separate, purify and characterize these species in native conditions without altering them while assuring a high throughput. This technological gap can be reduced by exploiting Asymmetrical Flow Field Flow Fractionation multidetection platforms (AF4 multidetection). Method: This work describes a complete set of strategies based on the AF4 system, from nanoparticle synthesis to separative method optimization to conjugates screening and characterization, achieving quantitative control and purification of ready-to-use conjugated Gold nanoparticles and ensuring effectiveness in biosensing. Results and Discussion: AF4-multidetection was used to study AuNPs with different types of surface coating [Poly ethylene glycol, (PEG) and Citrate], their binding behaviour with protein (Bovine serum albumin, BSA) and their stability after conjugation to BSA. A robust but flexible method was developed, able to be applied to different AuNPs and conjugating molecules. The morphology and conjugation mechanism of AuNPs-BSA conjugates were evaluated by combining online Multiangle light scattering (MALS) and offline Dynamic Light Scattering (DLS) measures, which provided an important feature for the quality control required to optimize bio-probe synthesis and subsequent bioassays.